INTEGRATED PRIMARY CARE MENTAL HEALTH QUALITY IMPROVEMENT INTERVENTION. Issue 12 (18th November 2016) - Cox, Joanne; Durant, Hannah; Castile, Natalie; Cheek, Sally; Dowd, Katherine; Carrick, Olivia; Reisinger, Ellen; Markiewicz, Molly; Caldas, Aldofo; Tunick, Rachel
Abstract : Background: About 20% of US children face mental health (MH) problems that interfere with functioning. Few receive treatment. Many providers (PCPs) screen for MH problems, but coordination systems are sparse. Objectives: To improve systems for identifying, assessing and treating children, 5–12 years old, presenting to primary care with MH problems, using an integrated QI intervention. To test whether an algorithm based stepped care model increases service enrollment. Methods: An interdisciplinary team starting 10/1/14 implemented the intervention using PDSA cycles. The stepped care model included identification of MH problems using structured screening, secondary assessment, triage to increasingly complex care levels: (1) PCP directed, (2) integrated SW or psychologist treatment, (3) community treatment and (4) specialty psychiatry. An algorithm directed PCPs to page SWs for same day assessments for anxiety, depression, grief, externalizing behaviors, and trauma. Control charts measured PCP compliance with the algorithm; secondary assessments and connection to treatment by 3 months. Results: Between 1/1/15 and 7/30/16, both PCP compliance with the algorithm and secondary screens showed special cause variation increasing from 56% to 92% and 38% to 58% respectively. Treatment enrollment increase out of control but fell in the last 2 measurement periods due to access barriers. Level of assigned care was PCP directed 16%, brief treatment 20%, community-based 47%, and specialty care 16%. Conclusions: An integrated MH model with same day SW assessments of children with positive MH screens shows promise for improving MH assessments. A referral algorithm directing stepped care assignments facilitated this process. Assess to community-based therapy was rate limiting.Figure 1 Figure 2 Figure 3 Figure 4